Pharsalus repandus Melichar, 1906 (Hemiptera, Ricaniidae): first record of ant-attendance in the family, ethological notes, and new records from Brazil - Domahovski, Alexandre Cruz; Paladini, Andressa (Zootaxa, 2024)
Ant attendance or trophobiosis is widely distributed in Auchenorrhyncha and can be deﬁned as a disjunctive association, an interspeciﬁc relationship between two symbiotic organisms. Aggregation behavior with or without ant mutualism has been documented for nymphs and adults in a few families of Fulgoromorpha whereas ant-attendance is reported for all planthopper families except for Ricaniidae. Based on field observations of Pharsalus repandus Melichar, 1906, the present work aims to record the first mutualistic interaction of ant-attendance in a species of the family Ricaniidae, report its aggregation behavior, its host plant, and expand its known distribution to the states of Paraná and Minas Gerais. Two ants were attending the planthoppers at the same time, identified as Camponotus (Myrmotrhix) rufipes (Fabricius, 1775) and Camponotus (Myrmobrachys) crassus Mayr, 1862. We noted direct contact and observed the ants employing antennal palpation behavior to stimulate the planthoppers to deliver honeydew.